PROGRAM BIMBINGAN DAN KONSELING DALAM MENGURANGI KECANDUAN GAME ONLINE OLEH SISWA KELAS VIII SMP MELATI BINJAI TAHUN PELAJARAN 2017/2018 - Tumiyem Tumiyem; Dessy Nita Br. Sembiring (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this research is to know the guidance and counseling program in overcoming the problems of the students who are addicted to online games, special programs to overcome the addiction of online games games and the willingness of students learning skill game online. This research was conducted at SMP Swati Melati Binjai, Jl. MT. Haryono, Ex. Jati Karya Kec. Binjai Timur Binjai City. The population in this study is the students of class VIII, amounting to 31 students. While the sample is the whole population of 31 students.From the results of the analysis of online game kecanduang prior to the guidance and counseling program with an average of 34.2 with a standard deviation of 5.5. From the results of the online game questionnaire analysis after the guidance and counseling program is known to average 38.8 with a standard deviation of 4.1. Both data are normally distributed. From these two variables it is concluded that the two data are homogeny.From the calculation results can be rhitung at 0.619 while the rtabel at the level of 5% of 0.349. so in conclude that the value rhitung> rtabel so Ho in rejected and Ha accepted. Because rhitung is in rejection area of Ho then Ha accepted. Ha accepted then